Eksperimentalna karakterizacija spreja in numerično modeliranje razprševanja suspenzije v razpršilnem sušilniku - Cajnko, Petra (Anali PAZU, 2023)
Drying is one of the most important and at the same time the oldest areas of process technology. One of the most established forms of drying is spray drying, which is very often present in the food, pharmaceutical and chemical industries. In this paper, we discuss the characterization of the spray formation on the spray nozzle and the implementation of numerical simulation with included secondary breakup of the spray. The characterization of the spray on the nozzle was performed on the Oxfor laser system, while the Ansys Fluent software package was used to perform the numerical simulations. A comparison of the results showed a good agreement between the particle size distribution obtained in the experiment and in the numerical simulation.
Keywords: eksperimentalna karakterizacija spreja; numerična simulacija; porazdelitev delcev; procesna tehnika; razpršilno sušenje; sekundarni razpad delcev